THE THEORETICAL FEASIBILITY OF STUDENT WORKSHEET BASED ON ACTIVE KNOWLEDGE SHARING ON THE HUMAN RESPIRATORY SYSTEMS MATERIAL FOR CLASS XI - DIAH RAHMAWATI (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2013)
Human respiratory system is material that related with process that happen in human. That material need higher comprehension that can be get from discussion and work together among students; therefore it is necessary to improve student activity to work together through particular strategy and student worksheet. One of active learning strategies that can improve student ability to work together is active knowledge sharing.The purpose of this research is to describe the theoretical feasibility of student worksheet which is oriented to active knowledge sharing on the human respiratory system material based on expert analysis. The research is refers to Four-D model that consists of four steps: define, design, develop, and disseminate. The result of this research showed that the theoretical feasibility of student worksheet based on expert analysis is 83, 68%. Keywords: student worksheet,active knowledge sharing, human respiratory system.